2017
DOI: 10.1016/j.drugalcdep.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of drunk and drugged driving behaviors four years post-college

Abstract: Background Driving under the influence of alcohol is a leading cause of injury and premature death among young adults, and college-educated individuals are at particularly high risk. Less is known about driving under the influence of other drugs, which is on the rise. Method This study describes prospective seven-year trends in alcohol and other drug (AOD)-involved driving among a young-adult sample beginning with their second year of college (i.e., Years 2–8), and documents the extent of continuity in such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 58 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…While this may simply reflect regression to the mean, in a separate analysis of the FYI cohort examining dual trajectories of mental health and alcohol use we found that the highest-risk drinking group also had a linear diminution in risky drinking behavior over the two-year study period (Goldstick et al, 2018), suggesting that "aging out" of high-risk behaviors may also be a factor. Alternatively, among 2 nd -year college students, Calderia et al identified declines in driving while specifically intoxicated/drunk or drugged-but not driving after drinking generally-suggesting "maturing" effects of particularly high risk behavior (Caldeira et al, 2017). Regardless, these findings-especially given the persistently high driving after drinking behaviors among the HDAD group at 24 months-support the ED's potential as a site for interventions to prevent intoxicated driving, and may inform their timing, targeting, and duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this may simply reflect regression to the mean, in a separate analysis of the FYI cohort examining dual trajectories of mental health and alcohol use we found that the highest-risk drinking group also had a linear diminution in risky drinking behavior over the two-year study period (Goldstick et al, 2018), suggesting that "aging out" of high-risk behaviors may also be a factor. Alternatively, among 2 nd -year college students, Calderia et al identified declines in driving while specifically intoxicated/drunk or drugged-but not driving after drinking generally-suggesting "maturing" effects of particularly high risk behavior (Caldeira et al, 2017). Regardless, these findings-especially given the persistently high driving after drinking behaviors among the HDAD group at 24 months-support the ED's potential as a site for interventions to prevent intoxicated driving, and may inform their timing, targeting, and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published repeated measures surveys of youth driving after drinking have provided insights into the contour of these behavioral trajectories, suggesting that youth who drive after drinking are highly likely to continue doing so. In an 8-year longitudinal study of a sample recruited as undergraduates, DAD increased significantly during the college years, with a plateau around modal age 22; further, more than 80% of those reporting DAD persisted with this behavior from preceding years (Caldeira et al, 2017). In another longitudinal undergraduate survey, driving after drinking frequency peaked at ages 22-23, with a 72% relative increase in the two weeks after respondents' 21 st birthdays (Fromme, Wetherill, & Neal, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…, 2017 ). A recent 7-year longitudinal study of incoming college students suggests that driving after drinking may be even more prevalent ( Caldeira et al. , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…After excluding students without access to a car, Caldeira and colleagues found that the prevalence of driving after drinking peaked at age 22 (66.9%) without any clear declines through age 24. Furthermore, driving after drinking persisted from year to year (83.9–89.1%) for 7 years, indicating that 8 or 9 out of 10 young adults who drive after drinking in a given year do so again in the subsequent years ( Caldeira et al. , 2017 ).…”
Section: Introductionmentioning
confidence: 99%